2017
DOI: 10.1016/j.nicl.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the structural connectome of the teenage brain revealed by generalized q-sampling MRI

Abstract: The question of whether there are biological differences between male and female brains is a fraught one, and political positions and prior expectations seem to have a strong influence on the interpretation of scientific data in this field. This question is relevant to issues of gender differences in the prevalence of psychiatric conditions, including autism, attention deficit hyperactivity disorder (ADHD), Tourette's syndrome, schizophrenia, dyslexia, depression, and eating disorders. Understanding how gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 74 publications
3
29
0
1
Order By: Relevance
“…Although that particular high-profile study has attracted controversy, other researchers have drawn similar conclusions (e.g. Jahanshad et al, 2011;Tunç et al, 2016;Tyan, Liao, Shen, Lin & Weng, 2017). Ritchie et al (2017) report stronger functional connectivity for males in unimodal sensorimotor cortices, and stronger connectivity for females in the default mode network.…”
Section: ! 4 Male Variability In General Intelligencementioning
confidence: 85%
“…Although that particular high-profile study has attracted controversy, other researchers have drawn similar conclusions (e.g. Jahanshad et al, 2011;Tunç et al, 2016;Tyan, Liao, Shen, Lin & Weng, 2017). Ritchie et al (2017) report stronger functional connectivity for males in unimodal sensorimotor cortices, and stronger connectivity for females in the default mode network.…”
Section: ! 4 Male Variability In General Intelligencementioning
confidence: 85%
“…We did not obtain the education years and cognitive tests, and no real patients were analyzed. Gender and education level were not analyzed, which were potentially associated with WM changes. In addition, the reconstruction parameters may be not optimal; the cohort of study participants was not large and these factors may have biased the results.…”
Section: Discussionmentioning
confidence: 99%
“…Creativity seems rooted in normative cognitive processes and neuronal representations apparently measurable by neuronal imaging techniques. Several studies have demonstrated a new and promising way to investigate aspects of creative thinking using neuroscientific methods (Thagard & Stewart, 2011;Tyan, Liao, Shen, Lin, & Weng, 2017). Particular brain areas have been identified with creativity.…”
mentioning
confidence: 99%
“…Recent evidence has demonstrated neurophysiologically determined gender differences regarding rewarding (Volf & Tarasova, 2013). Tyan et al (2017) reported gender differences in communication between brain areas: Brains of male teenagers seem to involve better intrahemispheric communication, brains of female teenagers for interhemispheric communication. The male network organization is more local, more segregated, and more similar to smallworld networks.…”
mentioning
confidence: 99%